PRECONDITIONS FOR THE SUCCESSFUL INTEGRATION OF DISABLED PERSONS INTO THE LABOUR MARKET - Baranauskienė, Ingrida; Dobrovolskytė, Ilona (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Low activity level of disabled persons is closely related to the lack of their vocational skills, qualification, experience and motivation. All of the above mentioned elements are interrelated and can be the cause of each other. The aim of the research – to create the grounded theory for the successful integration of disabled persons into the labour market after their vocational rehabilitation. The given paper presents a model for the successful integration of disabled persons into the labour market. The model can be further used in order to improve the vocational rehabilitation process and, consequently, increase the number of employed disabled persons. Such integration does not only improve the employment indicators of disabled persons but also contributes to their socialization and wellbeing.